Carbon Nanotubes in Cementitious Composites: Dispersion, Implementation, and Influence on Mechanical Characteristics. (31st October 2016) - Jarolim, Tomas; Labaj, Martin; Hela, Rudolf; Michnova, Kamila
Abstract : For effective utilization of nanoparticles in cementitious composite materials, their perfect dispersion is necessary. Appropriate quantity of ultrasonic energy (US energy), as well as usage of proper and compatible surfactant, is a prerequisite for carbon nanotubes' (CNT) suitable deagglomeration. US energy was supplied by Bandelin Sonopuls HD 3200 ultrasonic homogenizer. Influence of US energy's amount on CNT's dispersion in aqueous medium was monitored in two steps: at first roughly by an optical microscope and in the next step precisely by the measurement of absorbance via UV/Vis spectrophotometry. After the appropriate amount of US energy was found, cement mortars with CNT were prepared and tested. Their physical and mechanical properties were examined and compared to the reference specimens.